Retrospective monitoring of mercury in fish from selected European freshwater and estuary sites. (September 2015) - Nguetseng, Regine; Fliedner, Annette; Knopf, Burkhard; Lebreton, Benoit; Quack, Markus; Rüdel, Heinz
Graphical abstract: Highlights: Total Hg and Methyl-Hg were analyzed in bream from five rivers and one lake in Europe. Between 2007 and 2013 the environmental quality standard for Hg was exceeded at all riverine sites. Highest Hg levels were detected in the Rhône (FR), Göta älv (SE) and Western Scheldt (NL). Since 2007 THg and Methyl-Hg significantly decreased in bream from the Rhône estuary. The Methyl-Hg fraction of THg was always >80% and comparable at all riverine sites. Abstract: Levels and trends of total mercury (THg) and methylmercury (MeHg) compounds in bream ( Abramis brama ) from different European sites were compared. Bream were collected between 2007 and 2013 in the estuaries of the rivers Scheldt (Netherlands), Rhône (France), Göta älv (Sweden), Tees (United Kingdom), and Mersey (UK), and in Lake Belau (Germany). A direct mercury analyzer was used to determine THg concentrations while MeHg was measured by gas chromatography/inductively coupled plasma-mass spectrometry applying stable isotope dilution. THg and MeHg in annual pool samples of bream ranged between 15.9 and 251 μg kg −1 wet weight (ww) with lowest concentrations found at the reference site Lake Belau and highest in samples from the river Rhône. The EU environmental quality standard (EQS) of 20 μg kg −1 ww was exceeded at all sites and in all years except at Lake Belau in 2012. Significantly decreasing trends over time were observed only in bream from the Rhône, while THg increased in bream from the Western Scheldt. The MeHg fractions of THg were always >80% and a significant difference between sites was detected only in one case (Rhône vs . Lake Belau).